2012
DOI: 10.1044/1092-4388(2011/11-0058)
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Speech Recognition in Children With Cochlear Implants in a Virtual Classroom

Abstract: Direct connect testing with reverberant test materials allows assessment of speech recognition under conditions typical of classrooms and could be useful in identifying children with CIs whose performance decreases significantly in the presence of reverberation and noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
3
21
2
Order By: Relevance
“…These children with normal hearing attained a mean speech perception score of 80.1 (SD ¼ 1.8%), whereas the children in the current study attained a mean score of only 24.3 (SD ¼ 21.9%) with just their HA(s)/CI(s). These results are consistent with the findings of previous studies on speech intelligibility ability of students with hearing impairment in both simulated and actual classroom environments (Finitzo-Hieber & Tillman, 1978;Neuman et al, 2012). Given the poor SNRs that can be found in mainstream classrooms, these results are of significant concern (Crandell & Smaldino, 2000;Larsen & Blair, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These children with normal hearing attained a mean speech perception score of 80.1 (SD ¼ 1.8%), whereas the children in the current study attained a mean score of only 24.3 (SD ¼ 21.9%) with just their HA(s)/CI(s). These results are consistent with the findings of previous studies on speech intelligibility ability of students with hearing impairment in both simulated and actual classroom environments (Finitzo-Hieber & Tillman, 1978;Neuman et al, 2012). Given the poor SNRs that can be found in mainstream classrooms, these results are of significant concern (Crandell & Smaldino, 2000;Larsen & Blair, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, distance can directly affect the SNR for the student, resulting in poorer speech intelligibility. By reducing the distance between the student and the source of the target signal (53-4 meters), the effects of reverberation can be reduced (Crandell & Smaldino, 2000;Neuman et al, 2012).…”
mentioning
confidence: 99%
“…Neuman et al (2010) reported that children with typical hearing scored higher (poorer) SNR-50 scores in 0.6-s RT than that measured in the current study in the same RT. Neuman et al (2010), as a result, found smaller performance differences between children with typical hearing and those with cochlear implants (Neuman et al, 2012) compared to this study. Neuman et al (2010) presented speech prerecorded in 0.6-s RT binaurally through earphones to the children with typical hearing and, in Neuman et al (2012), as electro-acoustical input to the processors for those with implants, most bilaterally fitted, as compared to listening in a classroom in this study.…”
Section: Discussioncontrasting
confidence: 61%
“…The effects of reverberation and noise have been relatively less well understood with children with hearing loss (e.g., Picard & Bradley, 2001) and especially with those with cochlear implants (e.g., Neuman, Wróblewski, Hajicek, & Rubinstein, 2012) compared to children with typical hearing or adults. Finitzo-Hieber and Tillman (1978) found that children with hearing loss using a hearing aid benefited significantly from each reduction in RT from 1.2 to 0.4 to 0.0 s. Neuman et al (2012) reported on children with cochlear implants listening to the Bamford-Kowal-Bench Speech-in-Noise Test (BKB-SIN; Etymotic Research, Inc., 2005) and scored by 50% correct word recognition (SNR-50), the SNR in which a listener correctly perceives 50% of words. The children's scores declined (improved) significantly with each reduction in RT from 0.8 to 0.6 s to a nonreverberant condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation